2023
DOI: 10.1186/s13014-023-02199-3
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the patterns and pathways of local recurrence of nasopharyngeal carcinoma: evidence for individualized clinical target volume delineation

Abstract: Backgrounds Despite publication of international guidelines, there are notable controversial points of clinical target volume (CTV) delineation in nasopharyngeal carcinoma (NPC). Recently, scholars proposed a novel way of delineation of CTV in NPC—individualization of CTV delineation based on T classification and spread patterns, which yielded excellent long-term local control with limited late toxicities. The aim of this study was to clarify the anatomic patterns and pathways of local recurren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(34 reference statements)
1
0
0
Order By: Relevance
“…In the present study, the most common sites of local recurrence were the nasopharynx (93%) and skull base (53.7%), followed by the parapharyngeal space, prevertebral space, cavernous sinus, masticator space, and the pterygopalatine fossa. This is consistent with previous reports 6 , 18 , 19 . In 32 patients with rNPC after IMRT, Li et al reported recurrence rates of 78.1% and 59.4% in the nasopharynx and skull base, respectively; the authors also found significantly higher invasion rate of the ethmoid sinus in patients with rNPC than in patients with primary NPC 6 .…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, the most common sites of local recurrence were the nasopharynx (93%) and skull base (53.7%), followed by the parapharyngeal space, prevertebral space, cavernous sinus, masticator space, and the pterygopalatine fossa. This is consistent with previous reports 6 , 18 , 19 . In 32 patients with rNPC after IMRT, Li et al reported recurrence rates of 78.1% and 59.4% in the nasopharynx and skull base, respectively; the authors also found significantly higher invasion rate of the ethmoid sinus in patients with rNPC than in patients with primary NPC 6 .…”
Section: Discussionsupporting
confidence: 94%